Pemilihan Lokasi Terminal Barang di Kabupaten Semarang dengan Menggunakan Metode P-Median dalam Software Lindo 6.1 - Ocky Soelistyo Pribadi; Yulia Permatasari (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2021)
ABSTRACTSelection of Goods Terminal Locations in Semarang Regency by Using the P-Median Method in Lindo 6.1 . Software: Goods distribution activities in the Semarang Regency area often encounter obstacles in the form of limited road classes and road widths in the existing road network system. Violations occur against road class provisions because large-sized goods vehicles pass on roads of low class. In addition, it is often found that loading and unloading of goods is carried out on the side of the road and parking of goods vehicles when vehicle crew need to rest on the side of the road. The solution to this problem is found in the Regulation of the Minister of Transportation Number PM 102 of 2018 concerning the Operation of a Goods Terminal, where the goods terminal is a place to carry out loading and unloading of goods, intramodal and intermodal movement of goods transport, consolidation of goods/centerslogistics activities, and/or a car park for goods.The exact location needs to be analyzed based on the optimization of the characteristics of the road network and the operationalization of traffic with the parameters of distance, travel time and average speed of travel of goods vehicles to travel between sub-district centroids. The analysis was carried out with the help of QGIS software to obtain the characteristics of the road network and the value of traffic operationalization performance parameters, then the location selection of the candidate 12 sub-districts in Semarang Regency was carried out using the P-Median method in the Lindo 6.1 software. The result is that the optimal Tuntang District was selected from the analysis of the distance and time variables to be used as the location for the construction of the Goods Terminal in Semarang Regency. Keywords: location selection, goods terminal, QGIS software, P-Median method, Lindo 6.1 software.ABSTRAKKegiatan distribusi barang di wilayah Kabupaten Semarang sering menemui hambatan berupa keterbatasan kelas jalan dan lebar jalan pada sistem jaringan jalan yang ada. Pelanggaran terjadi terhadap ketentuan kelas jalan karena kendaraan barang ukuran besar melintas di jalan yang kelasnya rendah. Selain itu, sering didapati adanya kegiatan bongkar muat barang yang dilakukan di tepi jalan dan parkir kendaraan barang untuk beristirahat awak kendaraan di tepi jalan. Solusi masalah tersebut ditemukan pada Peraturan Menteri Perhubungan Nomor PM 102 Tahun 2018 tentang Penyelenggaraan Terminal Barang, dimana terminal barang itu adalah tempat untuk melakukan kegiatan bongkar muat barang, perpindahan intramoda dan antarmoda angkutan barang, konsolidasi barang/pusat kegiatan logistik, dan/atau tempat parkir mobil barang. Lokasi yang tepat perlu dianalisis berdasarkan optimalisasi karakteristik jaringan jalan dan operasionalisasi lalu lintas dengan parameter jarak, waktu tempuh dan kecepatan rata-rata perjalanan kendaraan barang untuk menempuh antar centroid kecamatan. Analisis dilakukan dengan bantuan software QGIS untuk mendapatkan karakteristik jaringan jalan dan nilai parameter kinerja operasionalisasi lalu lintas, kemudian pemilihan lokasi dari kandidat 12 kecamatan di Kabupaten Semarang dilakukan dengan metode P-Median dalam software Lindo 6.1. Hasilnya adalah terpilih Kecamatan Tuntang yang teroptimal dari analisis variabel jarak dan waktu untuk dijadikan lokasi pembangunan Terminal Barang di Kabupaten Semarang.Kata Kunci: pemilihan lokasi; terminal barang; software QGIS; metode P-Median; Software Lindo 6.1